Evolution and structure psicolingüística of the poetic function of the language - Gonzáles Moreyra, Raúl (2004)
OBJECTIVE: To explore significant for our problems they would be the following ones: a) The global processing of the emission like a textual unit. b) the processing of equivalences type 11 phonics. el the processing of semantic equivalences type 11. d) the processing of morfo¬syntactic equivalences type 1. DESIGN: Descriptive comparative of cross section. MATERIAL And METHODS: The technique of «cloze» was used to explore the poetic text reading (fables) in 200 children between the 7 and 16 years. The completion were described following the characterization as Jakobson and Levin on the poetic function like phonological, semantic and morfo-syntactic equivalences. RESULTS: AII the correlations are significant statistically with one p < 0,01, except for the one of metric that has one p < 0.05. The variables age and yield highly are correlated. The global score that is additions of the four dimensions has a coefficient «rho» of 0,90 that expresses the high association between both variables. CONCLUSIONS: The results demonstrate the evolutionary character of the performances of the children with respect to this function and the parallel ism of its development with the stages piagetana logical-makes specific and logic-formal.